INTERPRETASI ILMU DAN IMAN PERSPEKTIF PENDIDIKAN ISLAM IBNU SINA - Ariani, Windi; Putu Muchtar, Nicky Estu (Prodi Pendidikan Agama Islam Sekolah Tinggi Agama Islam Daruttaqwa Gresik, 2024)
The purpose of this study is to describe the understanding of science and faith from Ibn Sina's perspective in the context of Islamic education. This research delves deeper into Ibn Sina's concepts of Islamic science, faith, and education. Ibn Sina believed that knowledge and faith are interrelated and complementary by using the Intellect which in its scheme can enable progress through various levels of understanding and can ultimately lead to God or the ultimate truth. This study uses a qualitative method with the data collection technique being library research. The results of the study show that in understanding science and faith in the context of Islamic education, Ibn Sina encourages holistic education where one must understand science and faith thoroughly. The application of holistic education includes the adjustment of the educational curriculum based on the age level of the students, the development of individuals with three main elements (al-Jism 'physical', al-Nafs 'mental', and al-'Aql 'intellectual'), the formation of students' character (ethics and morals), and critical thinking to reflect on their knowledge and beliefs about God in a way that combines knowledge and faith so that it can be applied in the context of modern education.